The Relationship between Confidence and Public Speaking Anxiety in UNM Psychology Students who Join Organizations on Campus - Fatimah, Khusnul; ., Widyastuti (Polteknik Ilmu Pemasyarakatan, 2024)
Abstract Self-confidence here plays a very important role in reducing the feeling of anxiety that arises when speaking both privately and when in front of many people. This research aims to determine the relationship between self-confidence and public speaking anxiety in UNM psychology students who participate in organizations on campus. The sample for this research was UNM Psychology students who participated in organizations on campus, totaling 111 people. This research uses two scales as measuring tools, namely the self-confidence scale and the public speaking anxiety scale which are structured based on aspects of Lauster's self-confidence and the components of public speaking anxiety based on Rogers' theory. Based on the results of the analysis, it was found that there was a significant negative relationship between self-confidence and public speaking anxiety, r = -0.838 (p = 0.000). The higher the level of self-confidence, the lower the level of anxiety about speaking in public. The implication of this research is that students who join organizations can increase their self-confidence well so they do not experience anxiety about speaking in public. Keywords : Self-confidence, Speaking anxiety, Student organization